ANALISIS MANAJEMEN PERTANDINGAN SEPAK TAKRAW NOMOR DOUBLE EVENT: STUDI KASUS PENCAPAIAN MEDALI PERAK PADA POMNAS XIX JAWA TENGAH TAHUN 2025 - Aditya Ilham Maulana; Rola Angga Lardika; Hirja Hidayat (PT. Hasba Edukasi Mandiri, 2026)
The 19th National University Sports Week (POMNAS) in 2025 in Central Java serves as the premier sports competition for Indonesian university students. The sepak takraw discipline, particularly the doubles event, demands a perfect blend of physical ability, technique, and team strategy. This study aims to comprehensively analyze the match management and processes that led the Riau sepak takraw team to win a silver medal in the team doubles event. The method used is qualitative descriptive with a case study approach, in which the researcher is an active participant (athlete). Data were collected through participatory observation, documentation, and field notes during the selection process, preparation (General Preparation Phase and Specific Preparation Phase over 4 months), and the competition itself. The analysis revealed that the success in winning the silver medal was attributed to an open selection system, structured training periods, intensive training camps, and the team’s mental resilience. In the final round, the Riau team had to concede defeat to East Java with a score of 2-1. The conclusion of this study emphasizes that national achievements are the result of long-term commitment, discipline, team synergy, and the ability to manage competitive pressure. These findings provide practical contributions to the development of an evidence-based sepak takraw development model at the regional level.